The Role of Religiosity in Work-Life Balance - Salamiah Sari Dewi; Abd. Madjid; Aris Fauzan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Today's work scenario is characterized by a fast rate of change, intense pressure, constant decline, changing demographics, increasing use of technology have affected the lives of employees. A person working aims to find life-work balance in his personal life. Work-life balance has implications for attitudes, behavior, welfare and organizational effectiveness. Therefore, it is necessary to have an attitude of appreciation from a sense of diversity towards a religion and one's belief in the existence of God which is manifested by obeying His commands and prohibitions with all one's heart and soul which is called religiosity. Religious activities are closely related to religiosity, not only when performing rituals (worship), but also other activities including work. Thus, religiosity can predict a person's behavior at work. This article reviews the literature on the role of religiosity in the work-life balance domain for employees, which emphasizes the importance of work-life balance supported by the values of religiosity of the employees.